Factors influencing graduate’s intention to repay educational debt - Siti Safwanah Jumat@Mohameda; Haneffa Muchlis Gazali; Tamrin Amboala (Penerbit UMS, 2022)
This study examines the relationships between graduates' intention to repay educational debt and their attitude, parental influence, financial literacy, and financial behaviours. This study employs quantitative methods, and data was collected using a Google Form. The self-administered online survey received 258 responses in total. According to the findings, attitude, parental influence, and financial literacy all have a significant positive relationship with the intention to repay the loan. The financial behaviour has no discernible relationship to repaying the educational loan. According to the findings, the Theory of Reasoned Action was significantly associated with loan repayment. The study has limitations, and more research is needed to fully understand this phenomenon.